Numerical analysis of twin thickening process in magnesium alloys. (1st February 2017) - Siska, Filip; Stratil, Ludek; Cizek, Jan; Ghaderi, Alireza; Barnett, Matthew
Abstract: A finite element study of the stress field evolution around the { 10 1 ¯ 2 } tensile twin of different thickness in magnesium alloy is performed. The system is represented by the 2D models of one and three elastic elliptical inclusions with different aspect ratios surrounded by the plastic matrix. Anisotropic elasticity and crystal plasticity theory are used to describe the material behavior. Numerical results for single inclusion overestimate the initial stress for the stable twin aspect ratio by a factor of two compared to the experimental results. Multiple inclusions case obtains values closer to the experimental ones. Therefore it is concluded that the process of twin thickening cannot be solved within the analysis of the single inclusion and an interaction between twins in the same and neighboring grains plays a crucial role during the twin thickening process. Graphical abstract: Image 1